O jornal O Commercio como porta-voz do produtor arrozeiro (Cachoeira do Sul, 1905-1925) - Hammerschmitt, Alini (2019)
The current thesis looks onto the newspaper called O Commercio which circulated in the city of Cachoeira do Sul, in the early 20th Century. For this purpose, we selected newspaper articles in a corpus of twenty-five headlines published between 1905 and 1925. The overall aim of this paper is to verify the hypothesis that the O Commercio newspaper takes on the role of the rice sector’s advocate in the analyzed period. The specific goals are to examine the domination and power relations of the newspaper's positioning and analyze the journal's message. As a method, we opted to use John Thompson's hermeneutics to analyze media products. This author suggests that, firstly, a socio-historical analysis should be done and afterward a formal discursive analysis, in order to then do the interpretation/reinterpretation. Within that framework, we can affirm a possible confirmation of the hypothesis that the O Commercio newspaper, in the studied term, may be seen as an advocate of the rice sector in Cachoeira do Sul. Likewise, by the verification of the newspaper’s conveyed messages, we can state that in that context, the journal’s enunciation counted for pursuing and maintaining domination relations.